Carboplatin Dosing in Ovarian Cancer: Problems and Pitfalls. Issue 7 (1st October 2011) - Collins, Ian M.; Roberts-Thomson, Rachel; Faulkner, David; Rischin, Danny; Friedlander, Michael; Mileshkin, Linda
Abstract : Objective: Carboplatin is one of the most effective chemotherapeutic drugs for the treatment of ovarian cancer. It has simple pharmacokinetics and a predictable toxicity profile. The dose can be calculated effectively based on a patient's renal function as defined by the glomerular filtration rate (GFR). The measurement of the GFR is best done using radioisotopes, but this is expensive and not widely available, so many centers use equations to estimate GFR based on serum creatinine and other easily measured data. Recent changes in the measurement of serum creatinine, and a move toward isotope dilution mass spectrometry standardized values, have highlighted the difficulty in safely and effectively calculating doses of carboplatin in patients with ovarian cancer. Methods: We have evaluated the currently available evidence for the most common methods of estimating and measuring GFR. We explored the problems and pitfalls with using each of these methods or equations and examined the effects of small changes in clinical parameters and the effect on carboplatin dose. Results: Previous studies evaluating carboplatin's toxicity and efficacy used various different methods of GFR estimation and older methods of creatinine measurement. These may not translate to use with newer laboratory methods and may result in higher delivered doses than anticipated. Conclusions: The lack of consistency in carboplatin dosing, and changing creatinine values are a cause for concern if patient toxicity is a possible outcome. The need for new studies using new standard methods that can be widely used are urgently required to provide clarity in this area.